“Less is more?” The association between crop specialization and dietary diversity in China - Cao, Shouhui; Sun, Fei; Wang, Lijun; Hong, Weihua (Frontiers in Sustainable Food Systems, 2024)
Dietary diversity is an important indicator used to measure family dietary quality and food safety status. Against the backdrop of the transformation of China’s agricultural production model from a diversified, small-scale approach to specialization, this paper presents a comprehensive investigation into the complex interrelationship between crop specialization and dietary diversity. It employs a multi-method approach, integrating theoretical insights with empirical evidence. The analysis is based on a micro-survey of 866 rural households, utilising mediation, moderation, and unconditional quantile regression model. The results indicated that crop specialization had a notable negative impact on dietary diversity, particularly among II part-time and mountainous households. Further analysis of the mechanisms involved reveals that income exerts a mediating effect, while education and market factors exert a moderating effect. Such factors may serve to mask or reduce the negative effects of crop specialization on dietary diversity. In the reality that the trend of production specialization is irreversible, government interventions to ensure dietary diversity and food security for rural households, particularly II part-time households and those in mountainous regions, can be implemented in three key areas: income support, education enhancement, and market access improvement.